Does 10mg versus 12.5mg of 0.5% hyperbaric bupivacaine influence the incidence of epigastric discomfort encountered during caesarean section under spinal anesthesia? - Rehana Feroze, Aftab Hussain, Faisal Wahid, Muhammad Tariq, Muhammad Asif Saleem, Abdul Wasay Toor (Journal of Rawalpindi Medical College, 2022)
Objective: To determine effect of two different volumes of 0.5 % hyperbaric bupivacaine in relation to epigastric discomfort during Cesarean section under spinal anaesthesia.